Molecular identification of diarrheagenic Escherichia coli pathotypes and their antibiotic resistance patterns among diarrheic children and in contact calves in Bahir Dar city, Northwest Ethiopia - Belete, Mequanint Addisu; Demlie, Tiliksew Bialfew; Chekole, Wagaw Sendeku; Sisay Tessema, Tesfaye (PloS one, 2022)
Diarrheagenic Escherichia coli strains are an essential cause of diarrheal infection in younger children and animals. The study was focused on understanding the associated characteristics of various DEC strains among children and calves, establishing the possible zoonotic transmission, and determining their antibiotic resistance patterns. Samples from 144 acute diarrheic children and 50 diarrheic calves were collected and processed using traditional culture methods. The molecular identification of pathotypes was completed using primer-specific polymerase chain reaction (PCR) targeting ten virulence genes ( stx1 , stx2 , eae , aatA , lt , st , ial , hlyA bfpA , and daaE ) related to six DEC pathotypes (EPEC, ETEC, EHEC, EAEC EIEC, and DAEC). The antimicrobial susceptibility testing was carried out using the Kirby-Bauer disk diffusion method. Colonies from 74 study subjects (54 diarrheic children and 20 diarrheic calves) were positive for E . coli isolates. Subsequent PCR detection discovered that 77% of children and 85% of calves’ isolates were positive for one or more virulence genes typical of particular strains. Among those ETEC [(18%), (26%)] is being the maximum predominant, and [(15%), (15%)] were positive for STEC, [(13%), (8%)] for atypical EPEC, [(6%), (7%)] for EHEC, [(6%), (5%)] for EAEC, and [(6%), (4%)] for EIEC strains in children’s and calves, respectively. Of the identified E . coli isolates, about 29% were found to be hybrid isolates. ETEC (66.7%) and STEC (58.9%) strains showed a better detection rate in contact children with diarrheic calves than children with no contacts. Most antibiotic resistances were obtained towards amoxicillin (64.9%), gentamycin (56.8%), and ampicillin (54.1%). Up to sixty-five percent of isolates were resistant to a minimum of three categories of antibiotics. This is the primary report on the wide occurrence of the six-diarrheagenic Escherichia coli strains, and ETEC was found to be the predominant pathotype among children and contact calves in Ethiopia.